Wild populations of Agave angustifolia (Asparagaceae) from Sonora, Mexico: morphological variation and sugar content - Fragoso-Gadea, Tania; Gutiérrez, Aldo; Coronado , Martha Lizett; Terrazas , Teresa; Ramos-Clamont , Gabriela; Vázquez-Moreno, Luz; Álvarez-Bajo, Osiris; Esqueda, Martín (Instituto de Ecología, A.C., 2021)
Background and Aims: “Bacanora” is a spirit drink that uses mainly wild populations of Agave angustifolia as raw material, which require conservation strategies due to their overuse. The aim of this work was to evaluate the morphological variation and the content of total reducing sugars and fructans in the stem of A. angustifolia in conserved wild populations from Sonora, Mexico.Methods: Three conserved wild populations of A. angustifolia were studied by 29 variables related to morphological characters, phenological maturity indicators, and the content of reducing sugars and fructans.Key results: The content of fructans and total reducing sugars in the stem presented an average of 22.6 and 32.7 g/100 g (dry basis) respectively, with a significant variation among wild populations (p<0.05). Of the 29 variables evaluated, a principal component analysis indicated that 51.9% of the data variance is explained with four components. A discriminant canonical analysis with the 16 variables that showed the greatest relationship with the four main components defined the grouping of the populations. Two canonical functions significantly separated (p<0.001) the three wild agave populations and represented 100% of the total variance.Conclusions: The variables with the greatest contribution and relative importance associated with each population were the development of the inflorescence, the content of total reducing sugars in the stem, as well as the tone and color saturation of leaves.